Probiotics And Infectious Agents - BHARAT MENGI; S.K.KOTWAL; MANINDER SINGH (International Journal of Pharma and Bio Sciences, 2011)
A well known adverse effect of the use of antibiotics as growth promoters/ chemotherapeutics often used indiscriminately for controlling infections is the emergence of antibiotic resistance strains, referred to as ’superbugs’. Antibiotic resistance is of great concern for scientists and medical professionals across the globe, and accordingly WHO recommends the use of alternative methods in order to curb the further emergence of antibiotic resistance strains. One such alternative and promising emerging concept is that of ’probiotics’. Probiotics have been found to have protective effects on infectious agents like Salmonella, E. coli, Shigella, Klebsiella, Proteus and many others in various in vitro and in vivo studies which have been reviewed in this article.